Loan Loss Provisioning of UK Commercial Banks Pre- and Post-Global Financial Crisis - Liang, Jiahui (2014)
This paper undertook a research on 29 UK commercial banks between the periods of 2006 to 2012 for observing the loan loss provisioning of the selected banks pre- and post- global financial crisis. There are two models were applied for this research, which are X-efficiency model and GMM model. We tested four hypotheses: 1) Do UK commercial banks conduct their provisioning relying on the business cycle? 2) Does income smoothing behaviour exist in the UK commercial banks? 3) Does capital management exist in the UK commercial banks? 4) Is Bank efficiency endogenous to loan loss provisioning? If yes / no, how does it correlate with loan loss provisioning? Our results showed no evidence for UK banks to conduct income smoothing and capital management through loan loss provisioning. However, we found a negative relationship between bank efficiency and loan loss provisioning and market concentration problem for the selected banks. The result suggests that the FCA should pay more attention to the loan portfolios of high market power banks.